2020
DOI: 10.1177/1934578x20921627
|View full text |Cite
|
Sign up to set email alerts
|

Plumbagin Induces Cell Cycle Arrest and Apoptosis in A431 Cisplatin-Resistant Cancer Cells

Abstract: The onset of drug resistance represents the leading cause of chemotherapy failure in clinics. In the last decades, natural compounds have emerged as possible anticancer strategies used either alone or in combination with chemotherapeutic drugs, in order to overcome drug resistance. In fact, plant-derived therapies present biological activity and minimal side effects showing promising roles in the resensitization of resistant cancer cells. This work was aimed at investigating the anticancer potential of the nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Plumbagin (5-hydroxy2-methyl-1,4-naphthoquinone) is another naphthoquinone extracted from the roots of Plumbago zeylanica L, which has significant antitumor activity in vitro. It is able to induce apoptosis and increase ROS production and to arrest the cell cycle in the S phase and G2/M phase through inhibiting the expression of hyperphosphorylated retinoblastoma protein (p-Rb) in both sensitive (A431wt) and cisplatin-resistant (A431/Pt) human cervix squamous carcinoma cell lines [ 231 ]. Wang et al demonstrated that tetramethylpyrazine can effectively reverse the MDR of Pumc-91/ADM and T24/DDP cells through inhibiting the expression of MRP1, GST, and Bcl-2 and increasing the expression of TPOP-II in a dose-dependent manner.…”
Section: Potential Mechanisms Of Plant-derived Natural Products In Th...mentioning
confidence: 99%
“…Plumbagin (5-hydroxy2-methyl-1,4-naphthoquinone) is another naphthoquinone extracted from the roots of Plumbago zeylanica L, which has significant antitumor activity in vitro. It is able to induce apoptosis and increase ROS production and to arrest the cell cycle in the S phase and G2/M phase through inhibiting the expression of hyperphosphorylated retinoblastoma protein (p-Rb) in both sensitive (A431wt) and cisplatin-resistant (A431/Pt) human cervix squamous carcinoma cell lines [ 231 ]. Wang et al demonstrated that tetramethylpyrazine can effectively reverse the MDR of Pumc-91/ADM and T24/DDP cells through inhibiting the expression of MRP1, GST, and Bcl-2 and increasing the expression of TPOP-II in a dose-dependent manner.…”
Section: Potential Mechanisms Of Plant-derived Natural Products In Th...mentioning
confidence: 99%
“…The use of these drugs is limited by the severity of the collateral and side effects and by the frequent onset of resistance due to different alterations of different molecular aspects during the course of treatment, leading to therapeutic failure and tumor relapse [ 60 , 61 , 62 , 63 ]. Numerous studies have focused on the effect of naturally derived compounds on platinum-resistant cancers in order to explore the potentiality of an adjuvant and integrative medicine [ 64 ]. The combination of resveratrol and platinum-based drugs presents synergic or additive effects increasing the chemosensitivity in various cancer cells, and this effect is mediated by different mechanisms of action of the phytoalexin, which cooperates with the drugs.…”
Section: Resveratrol As a Chemosensitizer Agentmentioning
confidence: 99%